Analysis of the Government's Crisis Communication Strategy Discourse to Defend Covid-19 - Surahmat, Anton; Dida, Susanne; Zubair, Feliza (Jurnal Komunikasi, 2021)
Crisis communication is one of the most important instruments in crisis management. Unfortunately, there is a lot of criticism about how the Indonesian government implemented its crisis communication strategy during the Covid-19 pandemic season. This study aims to uncover the government's crisis communication strategy from the perspective of Van Dijk's critical discourse analysis. Based on the Situational Crisis Communication Theory (SCCT), researchers study the structure of discourse in texts consisting of macro, superstructure, and micro. There were 6 press releases from President Jokowi, Minister of Health Terawan Agus Putranto, and Spokesperson dr. Achmad Yurianto was collected using a purposive sampling method to describe the government's crisis communication strategy at the beginning of pre-crisis and crisis. The results show a significant dynamic crisis communication strategy on how the government implemented it in the pre-crisis and crisis phases. In the pre-crisis phase, they were statements from public officials especially in this case coming from President Jokowi and Minister of Health Terawan Agus Putranto. Both of these statements tend to lead to Deny and Diminish's strategy while still delivering messages in the form of Adjustments and Instructive Information so that the public remains alert and calm. However, in the crisis phase, government communication shifted towards Diminishes' statement, in the view of Justification that the crisis was actually not so terrible and bad. This is the biggest idea that emerged in the statement of President Jokowi and Spokesperson dr. Achmad Yurianto. Broadly speaking, this phase also provides a greater perspective on projections of government policy in the Covid-19 arrangement.